Shareholders and Associates - Veress , Emőd (Joint Stock and Limited Liability Companies in East Central Europe, 2025)
References: Angheni, S. (2013) Drept comercial. Profesionişti-comercianţi. Bucureşti: C.H. Beck. Arsić, Z. (2007) ‘Ništavost odluka skupštine akcionarskog društva’, Pravo i privreda, 44(1–4), pp. 11–18. Arsić, Z. (2008) ‘Pojam skupštine akcionarskog društva, kvorum za rad i većina za donošenje odluka’, Zbornik radova Pravnog fakulteta u Novom Sadu, 42(1–2), pp. 133–144. Bohinc, R. (2008) Korporacije: razlaga pravnih pravil in sodna praksa. Ljubljana: Nebra. Buhala, O. (2022) Pravo spoločnikov na informacie. Praha: C.H. Beck. Căpăţînă, O. (1991) Instituţii ale noului drept comercial. Societăţile comerciale. Bucureşti: Lumina Lex. Cărpenaru, St. D. (2016) Tratat de drept comercial roman, 5th edn. Bucureşti: Universul Juridic. Cărpenaru, St.D., Piperea, Gh., David, S. (2014) Legea societăților. Comentariu pe articole, 5th edn. București: C.H. Beck. Catană, R., Șumandea-Simionescu, I. (2019) ‘Romania’ in Gerner-Beuerle, C., Mucciarelli, F.M., Schuster, E., Siems, M. (eds.) The Private International Law of Companies in Europe, 1st edn. München/Baden-Baden/Oxford: Beck/Nomos/Hart, pp. 509–538. Chomiuk, M. (2023) in Z. Jara (ed.) Kodeks społek handlowych. Komentarz. Warszawa: C.H. Beck/Legalis. Cileček, F., Ruban, R. (2017) ‘Nejvyšší soud České republiky: Účinky opětovného uplatnění návrhu na vyslovení neplatnosti (části) usnesení členské schůze’, Obchodněpravni revue, 2017/2, p. 50. Csach, K. (2021) ‘Právo spoločníka spoločnosti s ručením obmedzeným na informácie po R 44/2019’, Sukromne pravo, 7(4), pp. 137–144. Csach, K. (2022) ‘Digital corporate governance in Slovakia’, Pravny obzor, 105 (special issue), pp. 3–13. Csach, K., Havel, B. (eds.) (2017) Akcionařske dohody. Praha: Wolters Kluwer. David, S. (2014) in Cărpenaru, St.D., Piperea, Gh., David, S., Legea societăților. Comentariu pe articole, 5th edn. București: C.H. Beck, pp. 260–461. Duţescu, C. (2010) Drepturile acţionarilor, 3rd edn. Bucureşti: C.H. Beck. Fegyveresi, Zs. (2024) ‘A tagok/részvényesek’ in Fegyveresi, Zs. (ed.) Roman tarsasagi jog, 3rd edn. Cluj-Napoca: Forum Iuris. Flídr, J. (2023) ‘Prekluze informačních práv společníka s. r. o. a povinnost společnosti opatřit si společníkem požadovanou informaci (současně kritická glosa k rozsudku Nejvyššího soudu sp. zn. 27 Cdo 1385/2022)’, Obchodněpravni revue, 2023/2 [Online]. Available at: https://app.beck-online.cz/bo/chapterview-document.seam?documentId=nrptembsgnpw64s7gjpxgxzxg4xgwyju&refSource=toc (Accessed: 10 October 2025). Flídr, J. (2024) ‘K pravomocem předsedy zasedání valné hromady vyhlásit výsledek hlasování a posoudit splnění podmínek pro preventivní sistaci hlasovacích práv’, Pravni rozhledy, 2024/1–2, pp. 24–33. Georgescu, I. L. (1948) Drept comercial roman, vol. II. Bucureşti: Ed. Socec. Gheorghe, C. (2020) Tratat de drept comercial roman. București: C.H. Beck. Goergen, M. (2012) International Corporate Governance. Harlow: Pearson. Ivanjko, Š., Kocbek, M., Prelič, S. (2009) Korporacijsko pravo. Ljubljana: GV Založba. Jovanović, N., Radović, V., Radović, M. (2021) Kompanijsko pravo – Pravo privrednih društava, 2nd edn. Beograd: Pravni fakultet u Beogradu, Centar za izdavaštvo i informisanje. Kidyba, A. (2023) Kodeks społek handlowych. Komentarz. Tom I i II, 18th edn. Warszawa: Wolters Kluwer. Kovaříček, K. (2020) ‘Místo § 212 odst. 2 ObčZ v českém právním systému a hmotněprávní podmínky jeho aplikace’, Pravni rozhledy, (5) [Online]. Available at: https://app.beck-online.cz/bo/chapterview-document.seam?documentId=nrptem bsgbpxa4s7gvpxgxzrgyza (Accessed: 10 October 2025). Kozieł, G. (2020) Prosta społka akcyjna. Komentarz do art. 3001–30013⁴ Kodeksu społek handlowych. Warszawa: C.H. Beck. Lavický, P. et al. (2022) Občansky zakonik I. Obecna čast (§1–654). Komentář, 2nd edn. Praha: C. H. Beck. Mićović, M. (2018) ‘Savremeni pravni okvir za angažovanje akcionara’, Pravni život, 67(11), pp. 5–18. Modzelewska, K., Reszczyk-Król, K. (2023) in Z. Jara (ed.) Kodeks społek handlowych. Komentarz, 4th edn. Warszawa: C.H. Beck/Legalis. Mrázová, Ž. (2018) ‘Slovakia’ in Mock, S., Csach, K., Havel, B. (eds.) International Handbook on Shareholders’ Agreements: Regulation, Practice, and Comparative Analysis. Berlin: De Gruyter, pp. 539–566. Naworski, J.P. (2003) Komentarz do Kodeksu społek handlowych. Społka akcyjna i przepisy karne. Warszawa: LexisNexis Polska. Oplustil, K., Sokołowski, K. (2003) Komentarz do Kodeksu społek handlowych. Tom IV: Łączenie - Podział i Przekształcanie Społek Kapitałowych. Komentarz do art. 491–633. Warszawa: C.H. Beck. Ovečková, O. et al. (2022) Obchodny zakonnik. Veľky komentar, vol. I, 2nd edn. Bratislava: Wolters Kluwer SR. Ovečková, O., Csach, K., Žitňanská, L. (2020) Obchodne pravo: obchodne spoločnosti a družstvo. Bratislava: Wolters Kluwer SR. Pascu, M., Pârvu, L. N. (2005) ‘Convocarea adunării generale a asociaţilor de către instanţă’, Revista de Drept Comercial, 2005/4, pp. 63–64. Patakyová, M. et al. (2022) Obchodny zakonnik. Komentar, 1st edn. Bratislava: C.H. Beck. Petrović, S., Ceronja, P. (2019) Osnove prava društava. Zagreb: Narodne novine. Radović, M. (2022) ‘Kritička analiza pravila o identifikaciji akcionara u srpskom Zakonu o privrednim društvima’, Revija Kopaoničke škole prirodnog prava, 4(2), pp. 9–31. Rodzynkiewicz, M. (2018) in Opalski, A. (ed.) Kodeks społek handlowych. Komentarz. Warszawa: LexisNexis Polska. Roth, G.H., Kindler, P. (2013) The Spirit of Corporate Law: Core Principles of Corporate Law in Continental Europe. Baden-Baden, Oxford, and Munich: Nomos, Hart, C.H. Beck. Ruban, R. (2017) ‘O konstitutivní povaze návrhů na vyslovení neplatnosti usnesení nejvyšších orgánů kapitálových společností a družstev’, Obchodněpravni revue, 2017/11–12, pp. 305–313. Săuleanu, L. (2008) Societăţile comerciale. Adunările generale ale acţionarilor. Bucureşti: Editura Hamangiu. Schiau, I., Prescure, T. (2009) Legea societăţilor comerciale nr. 31/1990. Analize şi comentarii pe articole, 2nd edn. Bucureşti: Editura Hamangiu. Strzępka, J.A., Zielińska, E. (2009) Kodeks społek handlowych. Komentarz. Warszawa: C.H. Beck. Šuleková, Ž. (2016) ‘Ničotnosť uznesení valného zhromaždenia obchodnej spoločnosti – posun v slovenskej judikatúre?’, Sukromne pravo, 2(1), pp. 18–21. Susanu, C. A. (2018) Cadrul juridic societar. Repere naţionale şi europene. Bucureşti: Universul Juridic. Tuleaşcă, L. (2016) Drept comercial. Intreprinderile comerciale. Bucureşti: Universul Juridic. Vasiljević, M., Jevremović-Petrović, T., Lepetić, J. (2022) Kompanijsko pravo: Pravo privrednih društava. Beograd: Pravni fakultet Univerziteta u Beogradu. Veličković, J. (2019) Derivativna tužba: kompanijskopravna i procesnopravna analiza. Doctoral thesis. Beograd: Pravni fakultet Univerziteta u Beogradu. Zapadka, P. (2014) ‘Praktyczne zastosowanie art. 394 KSH’, Edukacja Prawnicza, 1, pp. 15–18.